Anatomy of an extinct magmatic system along a divergent plate boundary: Alftafjordur, Iceland - URBANI, STEFANO; TRIPPANERA, DANIELE; PORRECA, MASSIMILIANO; ACOCELLA, Valerio; Kissel, C. (Geophysical Research Letters, 2015)
Recent rifting episodes highlight the role of magmatic systems with propagating dikes on crustal spreading. However, our knowledge of magmatic systems is usually limited to surface observations and geophysical data. Eastern Iceland allows direct access to extinct and eroded deeper magmatic systems. Here we collected field structural and AMS (anisotropy of magnetic susceptibility) data on 187 and 19 dikes, respectively, in the 10-12 Ma old Alftafjordur magmatic system. At a paleodepth of ∼1.5 km, the extension due to diking is at least 1-2 orders of magnitude larger than that induced by regional tectonics, confirming magmatism as the key mechanism for crustal spreading. This magma-induced extension, inferred from the aspect ratio of the magmatic system, was of ∼8 mm/yr, lower than the present one. AMS data suggest that most of dikes have geometrically normal fabric, at least at the margins, consistent with prevalent subvertical magma flow and propagation.